La Chirurgie Foraine : Une Solution Aux Problemes D’acces Aux Soins Chirurgicaux Des Populations Rurales - Katanga Tchangai, Boyodi; Alassani, Fousseni; Amavi, Kossigan Ayi; Attipou, Komlan (European Scientific Journal, ESJ, 2016)
Assessment of the quality of care in surgical outreach programs is necessary to improve their reliability. Purpose: The purpose of this study is to evaluate the clinical results of a surgical outreach program involving large numbers of patients. Material and Method: Retrospective study of clinical data and outcomes of patients operated on within a surgical outreach held in Togo’s Central Region was carried out. Data was collected from patient’s files with a follow-up, of 2 years. Results: Two hundred and seventy seven patients (277) underwent 304 surgical procedures within the surgical outreach. The conditions were essentially made of hernias of the abdominal wall (89%). Cases of hydroceles, endemic goiter and uterine myo-fibroids were also managed. Spinal anesthesia was the most common procedure of anesthesia (75%). Day case surgery involved 165 patients (59.5%). A post operative morbidity was observed in 31 patients (11%) essentially made of hematoma 28 cases (9.2%) and parietal abscesses 20 cases (6.5%).There were no postoperative deaths. Conclusion: outcomes in this study encourage surgical outreach programs as reliable means to address surgery accessibility issues of rural populations in low incomes countries.